Polymerisation behaviour of water hyacinth-based bio-oil during heating up in the presence of oxygen-containing compounds. Issue 3 (June 2021) - Kadarwati, S; Farida, R; Kasmui; Harjono; Fardhyanti, D S; Dewajani, H
Abstract: Bio-oil is susceptible to repolymerisation due to its high content of reactive oxygen-containing compounds. In this work, the polymerisation of the bio-oil produced from fast pyrolysis of water hyacinth was investigated during heating-up at various temperatures (50-95°C) in the presence of extra oxygen-containing model compounds (methanol and sucrose) with various concentration (10-50 wt%). The coke formed during the heating was quantified. The stability and reactivity of the hyacinth-based bio-oil for 48-h storage in the presence and the absence of the oxygen-containing compounds was also evaluated. This study showed that the presence of methanol in the bio-oil during heating up could suppress the repolymerisation leading to coke formation even at a higher temperature. In contrast, coke formation was severe (18.94 wt%) during the bio-oil heating up in the presence of sucrose at higher temperature (95°C). The presence of sucrose in the bio-oil could possibly promote the repolymerisation leading to coke formation. The repolymerisation possibly continued to occur during storage indicated by the increase in the viscosity, density and coke propensity of the bio-oil with added 50 wt% of sucrose compared to a negligible change in those properties of that with added methanol.